SELECTION OF COLLECTIONS (FICTION) IN AN EFFORT FOR THE DEVELOPMENT OF THE COLLECTION IN THE LIBRARY OF AL IZZAH LPMIINTERNATIONAL ISLAMIC BOARDING SCHOOL BATU CITY OF EAST JAVA - Handiawan Angling Prayuda (Jurnal Pustaka Ilmiah, 2019)
The purpose of this study was to describe the selection of the collections in the library Al Izzah LPMI Batu, East Java. With the benefit of providing research solutions to do the selection collection in the library Al Izzah LPMI Batu City in East Java in overcoming obstacles faced about the selection of the collection. The type of research used in this study is a qualitative research technique of observation and interviews.Based on observations and interviews direct to the Library Manager Al Izzah LPMI stone town, East Java can be summed up as follows. First, the selection process for the collection activities (fiction) does not do any procurement of collection. This selection process was conducted using three tools of seletion i.e. using Catalog for publishers, Indonesia’s national bibliography, and reviews books. Second, the obstacles faced in the activity of a selection of fiction in the library Al Izzah LPMI batu City, East Java, is the lack of human resources, the difficulty of finding fiction collection shades of Islam, and is still limited to the choice of the equipment used